Effects of Lower Seed Rates and Seed Class on Seed Multiplication Ratio, Quality and Yield of (Hordium Distichous. L) Malt Barley Under Rain Fed Condition. - Shibe, Belayneh; Anbes, Tilaye (Food, Agriculture and Natural Resources - NETWORKS, 2025)
The average yield of barley in Ethiopia is lower (2.5 t ha-1), as compared to the genetic yield potential of the released varieties (4.0 t -5.0 t ha-1). This low productivity is due to several constraints such as delivery of small quantity, poor quality and lengthy newly released varieties of early generation seed. The experiment was conducted to determine the effects of seed rate and seed class on seed multiplication ratio, seed yield, and seed quality of malt barley at Debre Birhan from 2019 to 2020. An experiment consisted of a factorial combination of four seed rates (40, 60, 80, and 100) kgha-1 and three seed classes (breeder, pre-basic and basic) laid out in randomized complete block design with three replications. The results revealed that seed rates were significantly different (P<0.05) on seed yield and, seed multiplication ratio. On the contrary, all seed quality parameters evaluated were not significantly affected by seed rates and seed classes of malt barley. The maximum (71) and minimum (39) seed multiplication ratio were recorded from the lower seed rate 40kgha-1 and the recommended seed rate 100kgha-1 respectively. On the other hand, the maximum (3960.90kgha-1) and minimum (2844.70kgha-1) seed yield were obtained from the recommended seed rate 100kgha-1 and lower seed rate 40kgha-1 respectively. However, 40kgha-1has 8.5% yield penalty as compared to the recommended rate in the study area. Hence, seed rate as low as 80 kgha-1 could be used at the three seed classes of malt barley with the integration of high input and intensive agronomic management in the Debre Birhan district during main rain season production. When seed shortage occurs, seed rates as low as 60 kgha-1 can be used at the three seed classes of malt barley to accelerate early generation seed supply with the integration of high input and intensive agronomic management in the same areas and production season